EFFICACY OF CORONARY BYPASS AND RADIOFREQUENCY ABLATION IN ATRIAL FIBRILLATION PATIENTS WITH CHRONIC KIDNEY DISEASE - B. G. Iskenderov; O. N. Sisina; M. N. Mamedov (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the influence of kidney dysfunction on the efficacy of simultaneous coronary bypass grafting together with radiofrequency ablation (RFA) in patients with comorbid persisting atrial fibrillation (AF) and chronic kidney disease (CKD).Material and methods. Totally, 247 patients studied (156 men and 91 women) of the age 50-67 y.o. (mean — 60,5±6,7). Values of glomerular filtration rate (GFR) at baseline were from 60 to 45 ml/min/1,73 m2. In 12 months after operation in 160 (68,4%) patients values of GFR increased in average by 39,4% (p<0,001) and were >60 ml/min/1,73 m2(1st group) and in 74 (31,6%) patients the changes of GFR were no significant and retained at levels <60 ml/min/1,73 m2 (2nd group).Results. The absence of late recourses of AF without antiarrhythmic treatment in the 1st group was found in 73,8% patients and 58,1% in the 2nd (p=0,011). Also, in successful RFA in 12 months after operation, GFR was significantly higher, than in patients with returned AF independently from baseline CKD: 77,5±10,4 and 60,8±9,2 ml/min/1,73 m2, resp., (p<0,001). In 12 months after operation the dynamics of morphofunctional and electrophysiological parameters in the 1st group was higher than in the 2nd. There was direct correlation of GFR with effective refractory period values of the left atrium (r=0,65; p=0,006) and frequency threshold of ischemia inducing (r=0,53; p=0,012). In the 2nd group comparing to the first, acute coronary syndrome, ischemic stroke, long time persisting AF and thromboembolisms were diagnosed significantly more often and the need for indirect anticoagulants was more significant — 41,89% vs 25,0% (p=0,014), in planned hemodialysis — 6,75% vs 0% (p=0,005) and in implanting of cardiac pacemaker — 5,41% vs 3,13% (p>0,05).Conclusion. So the increase of GFR after the operation of coronary shunting together with RFA in patients with persistent AF and comorbid CKD is associated with sinus rhythm retention and benign cardiovascular prognosis.